Genetic variability of wild populations of invasive redclaw crayfish (Cherax quadricarinatus) von Martens 1868 across Peninsular Malaysia - Mohamad Zulkarnain Mohd Dali,; Muhammad Syafiq Aiman Mohd Nasir,; Aliyu Garba Khaleel,; Nor Ainsyafikah Madiran,; Norshida Ismail,; Ahmad Syazni Kamarudin, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The redclaw crayfish had been listed as an invasive species in Malaysia following the various negative impacts displayed on both environment and economy. The species are largely culture in Malaysia for food, but unluckily escaped and expands to several waterbodies across the country. For effective control management of redclaw crayfish species, a total of 52 wild samples were collected from six locations in Peninsular Malaysia and analyzed using a 16S mitochondrial DNA to assess their genetic diversity and introduction history. Five haplotypes were detected associated with an overall low genetic diversity (Hd = 0.385, π = 0.00133). A single genetic structure was detected with a phylogenetic relationship showing two clusters related to the haplotypes from Australia and Papua New Guinea. The finding of this study provides the basic data that will aid the appropriate Malaysian authorities for both monitoring and management strategies of redclaw crayfish in Peninsular Malaysia.